A Volumetric Analysis of the 1H NMR Chemical Shielding in Supramolecular Systems - Czernek, Jiří; Brus, Jiří (International journal of molecular sciences, 2021)
The liquid state NMR chemical shift of protons is a parameter frequently used to characterize host-guest complexes. Its theoretical counterpart, that is, the 1H NMR chemical shielding affected by the solvent (1H CS), may provide important insights into spatial arrangements of supramolecular systems, and it can also be reliably obtained for challenging cases of an aggregation of aromatic and antiaromatic molecules in solution. This computational analysis is performed for the complex of coronene and an antiaromatic model compound in acetonitrile by employing the GIAO-B3LYP-PCM approach combined with a saturated basis set. Predicted 1H CS values are used to generate volumetric data, whose properties are thoroughly investigated. The 1H CS isosurface, corresponding to a value of the proton chemical shift taken from a previous experimental study, is described. The presence of the 1H CS isosurface should be taken into account in deriving structural information about supramolecular hosts and their encapsulation of small molecules.
Keywords: protony; acetonitrily; B3LYP; izotopy uhlíku; nikl; železo; Solvents; Proton Magnetic Resonance Spectroscopy; Polycyclic Compounds; Carbon Isotopes; chemical shielding; rozpouštědla; magnetická rezonanční spektroskopie; Macromolecular Substances; X-Ray Diffraction; Acetonitriles; difrakce rentgenového záření; Iron; antiaromaticity; GIAO; normální rozdělení; Nickel; makromolekulární látky; Protons; polycyklické sloučeniny; Magnetic Resonance Spectroscopy; Normal Distribution; proton NMR; protonová magnetická rezonanční spektroskopie